Characterization of mortality and high-risk characteristics of thyroid cancer in Filipinos using the California Cancer Registry - Hsu, Robert; Tsai, Kai-Ya; Chennapan, Krithika; Wojcik, Katherine Y.; Lee, Alice W.; Nieva, Jorge J.; Liu, Lihua (Frontiers in Public Health, 2023)
Introduction: Filipinos are the third largest Asian American subgroup and have the highest incidence of thyroid cancer among all races. To better understand this racial/ethnic disparity in thyroid cancer affecting Filipinos we analyzed the California Cancer Registry (CCR) data in Filipino thyroid cancer cases from 1988-2018. Methods: 97,948 thyroid cancer cases in California from 1988-2018 (until 2015 for Asian subgroups) were evaluated. We examined the case distribution by sex, age at diagnosis, race/ethnicity including Asian ethnic subgroups, histology, TNM stage, tumor size, lymph node involvement, lymphovascular invasion, and multifocality. We also looked at treatment data including surgery and radiation including radioactive iodine therapy. We calculated age-adjusted mortality rates (AAMR) for each major racial group and each Asian ethnic subgroup. Binary logistic regression was used to determine the likelihood of high-risk characteristics and treatment when comparing Filipinos to other racial/ethnic groups. Kaplan-Meier Estimate was performed to evaluate thyroid cancer survival across all race/ethnicities. Multivariate Cox proportion hazards regression was performed to evaluate mortality risk from all causes of death by race. Results: There were 5,243 (5.35%) Filipino thyroid cancer cases in California from 1988-2018. Filipinos had the highest AAMR (1.22 deaths per 100,000) in 2015. Filipinos had a higher likelihood of Stage IV thyroid cancer compared with Non-Hispanic Whites, Non-Hispanic Blacks, Hispanics and nearly all Asian subgroups. Filipinos had a worse 5-year and 10-year overall survival (OS) than the combination of all other Asian/Pacific Islanders. Filipinos compared to Non-Hispanic Whites had significant mortality risk in overall and papillary thyroid cancer cases (Overall HR: 1.10, 95% CI 1.07-1.13, p<0.0001, Papillary HR: 1.11, 95% CI 1.07-1.14, p<0.0001) when adjusted for race/ethnicity, age, gender, socioeconomic status, and stage. When stratified by Charlson comorbidity score, Filipinos compared to Non-Hispanic Whites still had significant mortality risk (Charlson 0 HR: 1.07, 95% CI 1.02-1.11, p =0.0017, Charlson 1+ HR: 1.07 95% CI 1.002-1.14, p = 0.0434). Conclusions: Filipino thyroid cancer patients have higher incidences of high-risk pathological features and greater AAMR and mortality risk. These findings warrant further investigation into better understanding the connection between the greater incidence of high-risk characteristics and increased mortality in Filipinos.